Rapid 3D Patterning of Poly(acrylic acid) Ionic Hydrogel for Miniature pH Sensors. Issue 7 (8th December 2015) - Yin, Ming‐Jie; Yao, Mian; Gao, Shaorui; Zhang, A. Ping; Tam, Hwa‐Yaw; Wai, Ping‐Kong A.
Abstract : Poly(acrylic acid) (PAA), as a highly ionic conductive hydrogel, can reversibly swell/deswell according to the surrounding pH conditions. An optical maskless stereolithography technology is presented to rapidly 3D pattern PAA for device fabrication. A highly sensitive miniature pH sensor is demonstrated by in situ printing of periodic PAA micropads on a tapered optical microfiber.